Combining long‐acting bronchodilators with different mechanisms of action: A pharmacological approach to optimize bronchodilation of equine airways. Issue 4 (26th March 2018) - Calzetta, L.; Rogliani, P.; Pistocchini, E.; Mattei, M.; Cito, G.; Alfonsi, P.; Page, C.; Matera, M. G.
Abstract : The ultra long‐acting β2 ‐adrenoceptor agonist olodaterol plus the ultra long‐acting muscarinic antagonist tiotropium bromide are known to relax equine airways. In human bronchi combining these drugs elicits a positive interaction, thus we aimed to characterize this information further in equine isolated airways stimulated by electrical field stimulation (EFS) and using the Concentration‐Reduction Index (CRI) and Combination Index (CI) equations. The drugs were administered alone and together by reproducing ex vivo the concentration‐ratio delivered by the currently available fixed‐dose combination (1:1). The single agents elicited a significant ( p < .05) concentration‐dependent reduction in the EFS‐induced contractility, that was synergistically improved (CI 0.18) when administered in combination (0.9 logarithms more potent, 24% more effective than the monocomponents). The drugs mixture allowed a reduction in the concentration of olodaterol from ≃1 to ≃2.3 logarithms. A favorable CRI was detected also for tiotropium bromide, whose concentration can be reduced ≃1 logarithm at medium effect levels, remaining positive up to submaximal relaxant effect in the presence of olodaterol. The combination of tiotropium bromide/olodaterol allows the reduction in the concentration of the monocomponents to achieve airway smooth muscle relaxation, thus potentially decreases the risk of adverse events when these drugs are used to treat severe asthmatic horses.